FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK SEKS BERISIKO PENULARAN HIV/AIDS PADA IBU RUMAH TANGGA (STUDI KASUS DI WILAYAH KERJA PUSKESMAS BANDARHARJO, KECAMATAN SEMARANG UTARA) - Tri Uji Rachmawati; Laksmono Widagdo; VG Tinuk Istiarti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
HIV/AIDS is one of the diseases in the world that has no cure and is always experienced an increase in cases each year. Based on the risk factors for transmission of HIV/AIDS in Semarang, heterosexual transmission ranked first by 79% and according to the type of work in the case of HIV/AIDS, housewife occupies a number of cases occurred in 2015, namely by 19%. Semarang District North ranked first in total cases of HIV / AIDS is the highest in the city of Semarang (2011-2015) amounted to 83 cases. The purpose of this study is to analyze the factors associated with risky sexual practices spread of HIV/AIDS among housewives. Using a quantitative approach with cross sectional the type of study design. The instrument used in this study was a questionnaire. The population in this study were housewife in Bandarharjo Public Health Center amounted to 17.860 people and a sample of 100 people with non-probability sampling technique sampling is accidental sampling. Analysis of the data Chi-square test was used for bivariate analysis with significance level of 95%. Research of results showed that the factors associated with risky sexual practices spread of HIV / AIDS on Housewife is knowledge (p-value = 0,004), attitude (p-value = 0,001), the availability of health care facilities and infrastructure (p-value = 0,004), media access to information on HIV / AIDS (p-value = 0,001), family support (p-value = 0,048). As for age, education level, husband's occupation, history of STIs, and support health workers no association with risky sex practices spread of HIV / AIDS. Suggestions for this study, Bandarharjo Public Heath Center needs to conduct counseling program in order to providing information about VCT HIV/AIDS in health centers, and Semarang City Health Office should conduct education about HIV / AIDS more than 3 times in a year